BHINNEKA TUNGGAL IKA DAN KONFLIK SOSIAL; (KHAZANAH MULTIKULTURAL INDONESIA DI ERA POST TRUTH) - Muhammad Usman; Masduki Duryat; H. Moch Sholeh; Fahmi Arfan; Muchsin; Faisal; Ikramullah Zein (Kodepena Indonesia, 2021)
Indonesia is one of the largest multicultural countries in the world, this can be seen from the sociocultural and geographical conditions of Indonesia that are so complex, diverse and broad. As a plural and heterogeneous country, Indonesia has the potential for multi-ethnic, multicultural, and multi-religious wealth, all of which are potentials to build a large multicultural nation